Respon Kepuasan Mahasiswa Program Studi Komunikasi Dan Penyiaran Islam Angkatan 2018 Terhadap Pelayanan Staf Di Fakultas Ushuluddin, Adab Dan Dakwah - Hasnur; Haswinda; Anugrah Wijaya; M. Ryan J.S. Patintingan; Nur Afiah (Journal of Media and Communication Studies, 2022)
Service staff, which is a staff who takes care of service tasks in operational activities and provides assistance, support to a leader in carrying out his duties. In connection with this statement, it means that students feel happy or maybe not happy with the services they get from the expectations of students and the needs of students in higher education during their studies. Students are said to be customers because they pay for educational services to learn. In everyday life, human needs include health needs, security needs, and educational needs. The purpose of the researcher is to find out the satisfaction response of students of class 2018 of the Islamic Communication and Broadcasting Study Program to staff services at the Faculty of Ushuluddin, Adab Da'wah and to find out the quality of service received by active students of class 2018 at the Faculty of Ushuluddin, Adab and Da'wah. The method used is the research method. quantitative research with a survey approach. In this study, there were variables before and after the researcher used a closed questionnaire or an open questionnaire. But this time in the study using a closed questionnaire so that researchers get results from the respondents themselves in the form of percent figures (%) which resemble mathematical numbers. So the need for awareness, synergy, and concern for faculty staff towards students who need consultation and clarity regarding their lectures, not discriminating in terms of service, and trying to provide better facilities.